Keanekaragaman Vegetasi Agroekosistem Karet Masyarakat Dayak Kerabat di Desa Nanga Pemubuh Kecamatan Sekadau Hulu Kabupaten Sekadau - Riza Linda, Agustinus Harmono Rafdinal, (Universitas Tanjungpura, 2019)
The agroecosystem is an ecological system that exists within the agricultural environment and one of the natural systems that occur after it is formed by the human. The Dayak people plant local rubber and are left to grow without intensive care along with various types of pioneering plants, fruit trees and woody trees. The aim of the study is to determine the composition and vegetation. The method used in this study is purposive sampling. The results are that there are 36 species consisting of 33 genera and 23 families. Generally, there are 16 tree species, 17 pole species, 18 stake species, and 16 seedling species. The most dominant families in the Nanga Pemubuh Village in all growth rates comprise 3 families, namely Arecaceae, Dipterocaearpace, and Moraceae with each number including 4 types of vegetation. The diversity of vegetation species of rubber agroecosystem is rated as medium or stable values (H' tree = 2,339, H' pole = 2,294, and H' stake = 1,652). Uniformity of the vegetation species of rubber agroecosystem is relatively high 0.794-0.941 and there is no dominance (C) in all growth rates 0.107-0.224.